Formation of the Three-Layered Structure of the Amery Ice Shelf, Antarctica - Wakahama, Gorow; Budd, W.F. (Journal of Glaciology, 1976)
Abstract Extensive glaciological studies on the Amery Ice Shell have been conducted since 1962 by the Australian National Antarctic Research Expeditions (ANARE). Deep core drilling to the depth of 310 m was carried out in 1968 at the site GI on the shell in order to obtain the vertical ice temperature distribution and to collect ice cores over the whole depth of the bore hole. General core analyses have been conducted since 1970 under an Australia- Japan Cooperative Project in order to clarify the structure of the ice shelf in connection with its flow. It was found through these analyses that the Amery Ice Shelf consists of three layers of different origin, which are denoted the top, middle, and bottom layers. The top layer is formed by the in situ accumulation of snow on the shelf, the middle layer is glacier ice flowing from the Lambert Glacier, originating far inland on the Antarctic ice sheet, and the bottom layer is developed by the freezing of sea-water at the bottom surface. Numerical calculations were made of the formation processes of the three-layered structure of the ice shelf, in which the accumulation and the densification of snow at the top surface, the straining of the shelf, and the freezing of sea-water at the bottom surface were taken into account. The thicknesses of the top and the bottom layers at site G1 obtained from the present calculations agree well with (hose obtained from the core analyses. The freezing rate of seawater at the bottom surface of the ice shelf estimated from the temperature profile is approximately 0.5 m a -1 . This considerable growth of frozen sea-water at the base of the ice shelf results in water flowing out from under the ice shelf being more saline and warmer than that flowing in.